2002
DOI: 10.1086/343218
|View full text |Cite
|
Sign up to set email alerts
|

Athermalizing Refractive Optics with Fluid Lenses

Abstract: ABSTRACT. Astronomical optics may encounter a wide range of nighttime temperatures (∼Ϫ10ЊC to ϩ20ЊC) at mountaintop observatories. Complex refractive optics used in high-performance spectrographs and focal reducers may perform poorly at temperature extremes unless special care is taken in their design. Refocusing will not always restore image quality, and thermally induced focal length changes may introduce troublesome image motion. We describe the techniques that we have used to predict the thermal behavior o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The detailed camera model shows that this axial gradient peaks at 0.14ЊC. Epps & Fabricant (2002) have shown that 0.2ЊC gradients negligibly affect image quality and image scale.…”
Section: Temperatures and Temperature Gradientsmentioning
confidence: 90%
See 2 more Smart Citations
“…The detailed camera model shows that this axial gradient peaks at 0.14ЊC. Epps & Fabricant (2002) have shown that 0.2ЊC gradients negligibly affect image quality and image scale.…”
Section: Temperatures and Temperature Gradientsmentioning
confidence: 90%
“…Under extreme conditions at the MMT, we find that these gradients and offsets double. Epps & Fabricant (2002) have shown that these temperature gradients and temperature offsets in the optics have a negligible effect on image quality and image scale, even under extreme conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been some efforts to use the oil couplant as part of an athermalizing strategy, 51 although there may be easier ways to accomplish the same goal. The strong dn/dT effect that Epps and Fabricant mention could be something to check in other oil-coupled applications.…”
Section: Special Cases: Doublets With a Problematic Glassmentioning
confidence: 99%
“…Harland Epps suggested that we allow the coupling fluid interfaces to have a small amount of power. Because the LL5610 has a large negative dn/dT, these weak fluid lenses can be used to athermalize the optics (Epps & Fabricant 2002). Making this athermalization work in practice requires careful analysis and a detailed knowledge of the thermal properties of all the optical materials and the optics mounts.…”
Section: Optics Athermalizationmentioning
confidence: 99%